Hydrogels incorporating active compounds from traditional Chinese medicine for diabetic wound healing: mechanistic pathways and bioengineering progress - Zhang, Rui; Tan, Suk Fei; Wang, Ye; Wu, Junxue; Zhang, Chao (Frontiers in Cell and Developmental Biology, 2025)
Diabetic wounds, especially foot ulcers, pose significant clinical challenges due to persistent inflammation, oxidative stress, impaired angiogenesis, and a high risk of infection. Advanced therapeutic strategies are needed to actively modulate the wound microenvironment. Hydrogels incorporating bioactive compounds derived from Traditional Chinese Medicine (TCM), such as curcumin, baicalein, glycyrrhetinic acid, Astragalus polysaccharides, and Ganoderma lucidum polysaccharides, offer a promising integrative approach. These hydrogels combine the biological activities of TCM compounds with the advantages of a moist, biocompatible wound dressing. This review highlights recent advancement (2020–2025) in TCM-based hydrogels for diabetic wound healing focusing on the design of these materials (e.g., curcumin, baicalein, glycyrrhetinic acid, Astragalus and Ganoderma polysaccharides) and the development of stimuli-responsive delivery systems (e.g., pH, enzymes, temperature, glucose and possibly magnetic/electric fields). TCM-derived compounds can not only form or reinforce hydrogel networks but also impart therapeutic functions by modulating key cellular pathways involved in anti-inflammatory (NF-κB) and antioxidant responses (Nrf2/HO-1), angiogenesis (VEGF, PI3K/Akt), and tissue regeneration (TGF-β/Smad). Challenges in translating TCM-based hydrogles into clinical use, such as pharmacokinetic variability and stability of the active compounds, are also discussed. Furthermore, representative studies are critically compared to elucidate how different TCM–hydrogel systems enchance wound healing outcomes by improving tissue regeneration, accelerating wound closure, and combating infection through responsive release and localized delivery mechanism. TCM-based hydrogels offer a novel, multi-functional platforms to diabetic wounds. They represent a novel paradigm in chronic wound management. Continued interdisciplinary research and clinical translation of these integrative biomaterials could significantly advance precision regenerative therapy for diabetic patients.